Sample Perception Of Farmers In The Program "Low Staple Paddy" In The City Of Padang Case Study: Anugrah Farmer Group In Kuranji - Fikri, Usnul; Elfemi, Nilda; Rahmadani, Sri (Jurnal Mamangan, 2025)
The Affordable Staple Rice Program (BPM) is an agricultural innovation introduced by the Padang City Agriculture Office with the aim of reducing production costs while maintaining rice field productivity. This research is important because the success of an innovation is determined not only by technology but also by the perceptions of farmers, the primary users.This study aims to describe farmers' perceptions of the BPM Program in Kuranji Village. The research method used a qualitative approach with a case study. Informants were selected through snowball sampling, with the head of the Anugrah Farmers Group as the key informant, followed by farmer members, the surrounding community, and representatives from the Padang City Agriculture Office. Data were obtained through in-depth interviews, observations, and documentation studies, then analyzed using the Miles & Huberman interactive model.The results showed that farmers perceived the BPM program as providing tangible benefits, particularly in reducing production costs from an average of IDR 10,000,000 to around IDR 7,000,000 per hectare and increasing yields from 3.5 tons/ha to 4.1 tons/ha, although still lower than the previous average of 5.55 tons/ha. Farmers also find it easier to maintain their rice fields because the use of straw mulch reduces weeds and maintains soil moisture. However, challenges encountered in the field include limited labor, difficulties in initial adaptation to new methods, and the need for ongoing support. Overall, the BPM program is perceived as beneficial, but it still requires evaluation and improvement for sustainability and wider adoption.Keywords: Farmer Perception, BPM, Agricultural Innovation, Production Costs